Answer:
[tex][0,\infty)[/tex]
Step-by-step explanation:
We have been given that the height, h, of a ball that is tossed into the air is a function of the time, t, it is in the air. The height in feet fort seconds is given by the function [tex]h(t)=-16t^2+96t[/tex].
We are told that the height of the ball is function of time, which means time is independent variable.
We know that the domain of a function is all real values of independent variable for which function is defined.
We know that time cannot be negative, therefore, the domain of our given function would be all values of t greater than or equal to 0 that is [tex][0,\infty)[/tex].
Please help me with this question
Will mark brainliest
Thanks so much
Answer:
7
Step-by-step explanation:
In this case, you go by the GREATEST DEGREE TERM POSSIBLE.
I am joyous to assist you anytime.
Find the point on the sphere left parenthesis x minus 4 right parenthesis squared(x−4)2 plus+y squared 2 plus+left parenthesis z plus 6 right parenthesis squared(z+6)2 equals=44 nearest to a. the xy-plane. b. the point left parenthesis 7 comma 0 comma negative 6 right parenthesis(7,0,−6).
Answer:
a) It is the set of point in the the circumference with equation [tex](x-4)^2+y^2=8[/tex].
b) (10.6, 0, -6 )
Step-by-step explanation:
a) The centre of the sphere is (4,0,-6) and the radio of the sphere is [tex]\sqrt{44} \sim 6.6[/tex]. Since |-6|=6 < 6.6, then the sphere intersect the xy-plane and the intersection is a circumference.
Let's find the equation of the circumference.
The equation of the xy-plane is z=0. Replacing this in the equation of the sphere we have:
[tex](x-4)^2+y^2+6^2=44[/tex], then [tex](x-4)^2+y^2=8[/tex].
b) Observe that the point (7,0,-6) has the same y and z coordinates as the centre and the x coordinate of the point is greater than that of the x coordinate of the centre. Then the point of the sphere nearest to the given point will be at a distance of one radius from the centre, in the positive x direction.
(4+[tex]\sqrt{44}[/tex], 0, -6)= (10.6, 0, -6 )
Julie buys three notebooks. if each notebook cost 30 cent less,
she would have bought one more. How much did she pay for the three
notebooks?
Answer:
360 cents or $ 3.6
Step-by-step explanation:
Let x be the original cost ( in cents ) of each note book,
After reducing the price by 30 cents,
New cost of each book = x - 30,
According to the question,
3x = 4(x-30) ( ∵ total cost = number of books × cost of each book ),
3x = 4x - 120
3x - 4x = -120
-x = -120
x = 120
Hence, the cost of three books = 3 × 120 = 360 cents or $ 3.6
If f(x)= a* and f(3) = 125, find f(2). Assume a > 0. f(2)=0
Answer:
The value of f(2) is 25.
Step-by-step explanation:
Given,
[tex]f(x) = a^x[/tex]
[tex]\implies f(3) = a^3[/tex]
According to the question,
[tex]f(3)=125[/tex]
[tex]\implies a^3=125\implies a = (125)^\frac{1}{3}=5[/tex]
Hence the function would be,
[tex]f(x) = 5^x[/tex]
If x = 2,
[tex]f(2)=5^2\implies f(2)=25[/tex]
To find f(2), substitute x = 2 into the function f(x).
Explanation:To find f(2), we can substitute the value of x into the function f(x). From the given information, we know that f(3) = 125. So, substituting x = 3 into the function gives us:
f(3) = 0.25e^(-0.25(3))
Simplifying this expression gives us 125 = 0.25e^(-0.75). Rearranging the equation, we can find the value of a:
a = 125 / 0.25e^(-0.75) = 500e^(0.75)
Now, we can substitute x = 2 into the function f(x):
f(2) = 500e^(0.75)(0.25e^(-0.25(2))) = 500e^(0.75)e^(-0.5)
Simplifying this expression gives us:
f(2) = 125e^0.25
So, the value of f(2) is 125e^0.25.
Learn more about Finding the value of a function at a given point here:https://brainly.com/question/34178955
#SPJ3
The average salary for a doctorate is 39,000 less than twice that of someone with a bachelor's degree. Combined, a people (one with a denctorate, are with a bachelor's earn 1+126,000. Find the salary for each degree. 120.000 - - 39000 24 = 165,ooo.
Answer:
doctorate salary: d = $71,000
bachelor salary: b = $55,000
Step-by-step explanation:
doctorate salary: d
bachelor salary: b
relationship between b and d: d = 2b - $39,000
Unfortunately, your "1 + 126,000" could not be correct. I'm going to assume that the total of the two salaries is $126,000. If that's the case, then:
bachelor salary + (2 times bachelor salary less $39,000) = $126,000. In symbols,
b + 2b - $39,000 = $126,000
Consolidating the 'b' terms results in 3b - $39,000 = $126,000, and so:
3b = $126,000 + $39,000 = $165,000
Dividing both sides by 3 yields the bachelor salary: b = $55,000
Then the doctoral salary is 2b - $39,000 = 2($55,000) - $39,000, or $71,000.
Check: Does b + (2b - $39,000) = $126,000? Yes.
Then the doctoral salary is d = $103,000, and the bachelor salary $29,000
lim x rightarrow 0 1 - cos ( x2 ) / 1 - cosx The limit has to be evaluated without using l'Hospital'sRule.
Answer with Step-by-step explanation:
Given
[tex]f(x)=\frac{1-cos(2x)}{1-cos(x)}\\\\\lim_{x \rightarrow 0}f(x)=\lim_{x\rightarrow 0}(\frac{1-(cos^2{x}-sin^2{x})}{1-cos(x)})\\\\(\because cos(2x)=cos^2x-sin^2x)\\\\\lim_{x \rightarrow 0}f(x)=\lim_{x\rightarrow 0}(\frac{1-cos^2x}{1-cos(x)}+\frac{sin^2x}{1-cosx})\\\\=\lim_{x\rightarrow 0}(\frac{(1-cosx)(1+cosx)}{1-cosx}+\frac{sin^2x}{1-cosx})\\\\=\lim_{x\rightarrow 0}((1+cosx)+\frac{sin^2x}{1-cosx})\\\\\therefore \lim_{x \rightarrow 0}f(x)=1[/tex]
i need help finding this answer to this inequality -10[9-2x]-x≤2x-5
Answer:
x≤5
Step-by-step explanation:
-10(9-2x)-x≤2x-5
-90+20x-x≤2x-5
19x-2x≤90-5
17x≤85
x≤85/17
x≤5
Rephrase in contrapositive form:
(a) "If you are taller than 6 ft, then it is unpleasant for you to travel in economy class." Your contrapositive must not contain explicit references to negation. Assume that the negation of "unpleasant" is "pleasant".
(b) "If x ≥ 0 and y ≥ 0 then xy ≥ 0" where x, y are real numbers.
Step-by-step explanation:
Consider the provided information.
For the condition statement [tex]p \rightarrow q[/tex] or equivalent "If p then q"
The rule for Contrapositive is: Negative both statements and interchange them. [tex]\sim q \rightarrow \sim p[/tex]
Part (A) If you are taller than 6 ft, then it is unpleasant for you to travel in economy class.
Here p is "you are taller than 6 ft, and q is "it is unpleasant for you to travel in economy class".
It is given that Your contrapositive must not contain explicit references to negation. Assume that the negation of "unpleasant" is "pleasant".
Contrapositive: If it is pleasant for you to travel in economy class then you are not taller than 6 ft then.
Part (B) "If x ≥ 0 and y ≥ 0 then xy ≥ 0" where x, y are real numbers.
Here p is "xy≥ 0, and q is "x ≥ 0 and y ≥ 0"
The negative of xy≥ 0 is xy<0, x ≥ 0 is x<0 and y ≥ 0 is y<0.
Remember negative means opposite.
Contrapositive: If xy < 0 then x<0 and y<0.
Final answer:
The contrapositive of a statement involves switching the positions of the subject and the complement, and negating both.
Explanation:
To rephrase the given statement in contrapositive form, we need to switch the positions of the subject and the complement, and negate both.
(a) The contrapositive of the statement 'If you are taller than 6 ft, then it is unpleasant for you to travel in economy class' is:
'If it is pleasant for you to travel in economy class, then you are not taller than 6 ft.'
(b) The contrapositive of the statement 'If x ≥ 0 and y ≥ 0 then xy ≥ 0' is:
'If xy < 0, then at least one of x or y is less than 0.'
g Define simple random sampling. Choose the correct answer below. A. Simple random sampling is the process of obtaining a sample of size n from a population of the same size n. The sample is then called a simple random sample. B. Simple random sampling is the process of using chance to select individuals from a population to be included in the sample. The sample is then called a simple random sample. C. A sample of size n from a population of size N is obtained through simple random sampling if every possible sample of size n has an equally likely chance of occurring. The sample is then called a simple random sample. D. Simple random sampling is the process of selecting individuals from a population using a convenient sample. The sample is then called a simple random sample.
Answer:
C. A sample of size n from a population of size N is obtained through simple random sampling if every possible sample of size n has an equally likely chance of occurring. The sample is then called a simple random sample.
Step-by-step explanation:
Simple Random Sampling is the sampling where samples are chosen randomly, where each unit has an equal chance of being selected in a sample.
Option A is incorrect as the size of the sample and size of the population is not the same generally if it does happen then there will be no difference between sample and population.
Option B is incorrect as Simple Random Sampling is not a chance it is a way that samples can be taken.
Option D is incorrect as when samples are taken using a convenient sample then it is called Convenient Sample, not Simple Random Sample.
Thus, only option C is correct.
Simple random sampling is a method where each possible sample from a population has an equal chance of being chosen. This ensures that all members of a population have an equal opportunity of being in the sample, thus representing the population accurately. It differs from other sampling techniques like convenience sampling, stratified sampling, cluster sampling and systematic sampling.
Explanation:Simple random sampling can best be defined as the process in which each member of a population initially has an equal chance of being selected for the sample. In other words, a sample of size n from a population of size N is obtained through simple random sampling if every possible sample of size n has an equally likely chance of occurring. This sample is then called a simple random sample. An example of this process may be selecting the names of students from a hat for a study group, where each student from the class(population) has an equal chance of being selected.
On the contrary, it should not be mistaken with convenience sampling, which is a non-random method of choosing a sample that can produce biased data. Other variants of random sampling include, but not limited to, stratified sampling, cluster sampling, and systematic sampling.
Overall, simple random sampling is a vital and simple method part of statistics to represent a population accurately for a study.
Learn more about Simple Random Sampling here:https://brainly.com/question/33604242
#SPJ12
A new building that costs $1,000,000 has a useful life of 25 years and a scrap value of $600,000. Using straight-line depreciation, find the equation for the value V in terms of t, where t is in years. (Make sure you use t and not x in your answer.)
V(t) =
Find the value after 1 year, after 2 years, and after 20 years.
Value after 1 year $
Value after 2 years $
Value after 20 years $
Answer:
The equations for the value V in terms of t is [tex]V(t)=-16000\cdot t+1000000[/tex] and the value of the building
after 1 year is $984,000
after 2 years is $968,000
after 20 years is $680,000
Step-by-step explanation:
With the straight-line depreciation method, the value of an asset is reduced uniformly over each period until it reaches its salvage value(It is the value of the asset at the end of its useful life).
We know from the information given the year = 0 the building costs $1,000,000 and a the year = 25 it costs $600,000.
With this information, you can calculate the decrease in value of the building due to age. We use the slope of a line formula because is a straight-line depreciation.
If (0, $1,000,000) is the first point and (25, $600,000) is the second point. we have
[tex]m=\frac{V_{2} -V_{1}}{t_{2}-t_{1}} =\frac{600000-1000000}{25-0} =-16000 \frac{\$}{years}[/tex]
To find the equation for the value V in terms of t, we use the point-slope form, this expression let you calculate the value of the building at the end of the year (t)
[tex]V-V_{0}= m(t- t_{0})\\V-1000000=-16000(x-0)\\V=-16000\cdot t+1000000[/tex]
To find the value after 1 year, after 2 years, and after 20 years. We put the year into the equation [tex]V(t)=-16000\cdot t+1000000[/tex]
[tex]V(1)=-16000\cdot (1)+1000000=\$984,000\\V(2)=-16000\cdot (2)+1000000=\$968,000\\V(20)=-16000\cdot (20)+1000000=\$680,000[/tex]
A projectile is fired from a cliff 220 ft above water at an inclination of 45 degrees to the horizontal, with a muzzle velocity of 65 ft per secound. the height ,h, of the projectile abore water is given, h(x)=(-32x^2)/ ((65)^2 ) +x+220. x is the horizontal distance of the projectile from the face of the cliff. What is the maximum value of x?
Answer:
248.79 ft
Step-by-step explanation:
A projectile is fired from a cliff 220 ft above water at an inclination of 45 degrees to the horizontal, with a muzzle velocity of 65 ft per second.
[tex]h(x)=-\dfrac{32x^2}{65^2}+x+220[/tex]
For maximum value of x, h(x)≥0
[tex]-\dfrac{32x^2}{65^2}+x+220\geq0[/tex]
Solve quadratic equation for x
[tex]-\dfrac{1}{4225}(32x^2-4225x-929500)\geq0[/tex]
[tex]32x^2-4225x-929500\leq0[/tex]
Using quadratic formula,
[tex]x=\dfrac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex]
where, a=32, b=-4225, c=-929500
[tex]x=\dfrac{4225\pm\sqrt{4225^2-4(32)(-929500)}}{2(32)}[/tex]
[tex]x\geq-116.75\text{ and }x\leq 248.79[/tex]
Hence, The maximum value of x will be 248.79 ft
Final Answer:
The maximum horizontal distance x of the projectile from the face of the cliff, at the peak of its trajectory, is approximately 33.01 feet.
Explanation:
The maximum value of x occurs at the peak of the projectile's flight, which we can find by analyzing the given quadratic equation:
[tex]\[ h(x) = -\frac{32x^2}{v^2} + x + h_0 \][/tex]
For our specific problem:
[tex]\[ h(x) = -\frac{32x^2}{(65)^2} + x + 220 \\\\\[ \text{where} \\\\\[ h_0 = 220 \text{ feet (initial height)}, \\\\\[ v = 65 \text{ ft/s (muzzle velocity)}, \\\\\[ \text{angle of inclination} = 45 \text{ degrees}. \\\\[/tex]
The quadratic equation represents a parabola opening downward (since the coefficient of x² is negative), and the x-coordinate of the vertex of this parabola will give us the maximum value of x.
The x-coordinate of the vertex (maximum value of x) for a parabola in the form ax² + bx + c is given by the formula [tex]\( -\frac{b}{2a} \).[/tex]
In our equation:
[tex]\[ a = -\frac{32}{v^2} = -\frac{32}{(65)^2} \\\\\[ b = 1 \\\\\[ c = h_0 = 220 \][/tex]
Now we substitute values of a and b into the formula for the x-coordinate of the vertex:
[tex]\[ -\frac{b}{2a} = -\frac{1}{2 \times ( -\frac{32}{(65)^2} )} \][/tex]
With the computations already given:
[tex]\[ \text{Maximum value of } x = 33.0078125 \text{ feet} \][/tex]
This means that the maximum horizontal distance x of the projectile from the face of the cliff, at the peak of its trajectory, is approximately 33.01 feet.
Over the last 40 years, the percent decrease in egg consumption in the U.S. is 35%. Forty years ago, the average consumption was 400 eggs per person per year. What is the average consumption of eggs today?
Final answer:
To find the current average egg consumption, calculate 35% of the original consumption of 400 eggs, which is 140 eggs, and subtract that from the original to get 260. Therefore, the average consumption now is 260 eggs per person per year.
Explanation:
If we look back 40 years and find that egg consumption was 400 eggs per person per year, and there has been a 35% decrease in egg consumption, we can calculate the current average egg consumption. To do this, we find 35% of the original consumption:
Multiply 400 (original consumption) by 0.35 (35%) to find the decrease in consumption. This equals 140 eggs.
Subtract this decrease from the original consumption: 400 - 140 equals 260 eggs. Therefore, the average consumption of eggs per person per year in the U.S. today is 260.
These changes in dietary habits over the years mirror shifts in consumer tastes, as well as concerns about health and production costs, all of which can influence the demand for different food products.
How many cubic yards of soil are needed to fill a planter that is 20 feet long by 3 feet wide by 4 feet tall
To calculate the amount of soil needed, you must first calculate the volume in cubic feet (20 feet x 3 feet x 4 feet = 240 cubic feet) and then convert that volume to cubic yards by dividing by 27 (240 cubic feet ÷ 27 = 8.89 cubic yards). So, approximately 8.89 cubic yards of soil is needed.
Explanation:To find the volume needed to fill the planter, we use the formula to compute the volume of stack, which is length × width × height. The planter has a length of 20 feet, a width of 3 feet, and a height of 4 feet. So, multiplying these values: 20 feet × 3 feet × 4 feet = 240 cubic feet.
Finally, we need to convert cubic feet to cubic yards because soil is typically bought in cubic yards. Since 1 yard = 3 feet, 1 cubic yard = 3 feet × 3 feet × 3 feet = 27 cubic feet. Therefore, to convert 240 cubic feet to cubic yards, we divide that by 27: 240 cubic feet ÷ 27 = 8.89 cubic yards. So, you will need approximately 8.89 cubic yards of soil to fill the planter.
Learn more about Volume Calculation here:https://brainly.com/question/33318354
#SPJ3
To fill a planter that is 20 feet long, 3 feet wide, and 4 feet tall, we need 240 cubic feet of soil, which converts to approximately 8.888 cubic yards. Rounding up, we will need 9 cubic yards of soil.
Volume = Length × Width × Height
Here,
the dimensions are given as:
Length: 20 feet
Width: 3 feet
Height: 4 feet
So, the volume in cubic feet is:
Volume = 20 ft × 3 ft × 4 ft
= 240 cubic feet
Next, we need to convert this volume from cubic feet to cubic yards.
Knowing that there are 3 feet in a yard,
we use the conversion factor:
1 cubic yard = 3 × 3 × 3
= 27 cubic feet
So, we divide the total cubic feet by the number of cubic feet in one cubic yard:
240 cubic feet ÷ 27
= 8.888 cubic yards
Since you typically can't have a fraction of a cubic yard in this context, we might round up to ensure you have enough soil, resulting in 9 cubic yards of soil needed.
Show that (p v q) A (p Vr)-(q vr) is a tautology.
Answer:
The statement [tex](p\lor q) \land (\neg p \lor r)\Rightarrow (q \lor r )[/tex] is a tautology.
Step-by-step explanation:
To prove this statement [tex](p\lor q) \land (\neg p \lor r)\Rightarrow (q \lor r )[/tex] is a tautology we are going to use a truth table. A truth table shows how the truth or falsity of a compound statement depends on the truth or falsity of the simple statements from which it's constructed.
A tautology is a formula which is true for every assignment of truth values to its simple components.
We can see from the table that the last column contains only true values. Therefore, the formula is a tautology.
Find an equation of the circle that satisfies the given conditions. (Give your answer in terms of x and y.) Center at the origin and passes through (8, 1)
Answer:
The equation of circle is [tex]x^2+y^2=65[/tex].
Step-by-step explanation:
It is given that the circle passes through the point (8,1) and center at the origin.
The distance between any point and the circle and center is called radius. it means radius of the given circle is the distance between (0,0) and (8,1).
Distance formula:
[tex]d=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]
Using distance formula the radius of circle is
[tex]r=\sqrt{\left(8-0\right)^2+\left(1-0\right)^2}=\sqrt{65}[/tex]
The standard form of a circle is
[tex](x-h)^2+(y-k)^2=r^2[/tex] .... (1)
where, (h,k) is center and r is radius.
The center of the circle is (0,0). So h=0 and k=0.
Substitute h=0, k=0 and [tex]r=\sqrt{65}[/tex] in equation (1).
[tex](x-0)^2+(y-0)^2=(\sqrt{65})^2[/tex]
[tex]x^2+y^2=65[/tex]
Therefore the equation of circle is [tex]x^2+y^2=65[/tex].
The equation of a circle centered at origin and passing through the point (8,1) can be determined using principles of geometry. Calculate the radius using the Pythagorean theorem and then substitute it into the general equation of a circle (x-h)² + (y-k)² = r², where h and k are 0 since the circle is centered at the origin. The equation for the circle is x² + y² = 65.
Explanation:The subject of this question is a circle in mathematics, particularly geometric principles. The given condition is that the circle's center is at the origin and it passes through the point (8,1). From our understanding of a circle, we know that the radius is the distance from the center to any point on the circle. Since our center is at the origin (0,0), the radius r can be calculated using the Pythagorean theorem as the distance from the origin to the point (8,1), which is sqrt((8-0)² + (1-0)²) = sqrt(65). Therefore, the equation of the circle in terms of x and y based on its center (h,k) and radius r is (x-h)² + (y-k)² = r². Given that the circle's center is at the origin, h and k equal to 0, which simplifies the equation to x² + y² = r², or in our case, x² + y² = 65.
Learn more about Circle Equation here:https://brainly.com/question/29288238
#SPJ3